(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Both Type II diabetes mellitus and osteoporosis are prevalent diseases at middle aged patients and both are associated with significant morbidity and mortality but the relationship between diabetes and osteoporosis is controversial . Objective: To determine that if patients with type 2 diabetes (T2DM) at increased risk of development of osteoporosis and whether T2DM was associated with a low bone mineral density (BMD). Methods: 50 osteoporotic patients aged 50 years and older and were asked whether having T2DM for more than 10 years or not as a case group, another 50 patients non-osteoporotic patients and were asked whether having T2DM for more than 10 years or not as control group, both samples were recruited from rheumatology consultant department at Ibn Sena Teaching Hospital. All patients received a standardized questionnaire on osteoporosis risk factors and biochemical tests (include level of blood sugar) were done to all of them to exclude renal and liver disease. Diabetic patients are evaluated for presence of proteinuria and retinopathy; all patients were evaluated for bone mineral density (BMD, by using a dual energy X-ray absorptiometry). Result: In this study T2DM was not a risk factor for osteoporosis as p- value (0.687).There is no significant differences between both gender p- value( 0.629) and no significant difference was found among smokers p-value 0.05.there is neither significant difference among two groups regarding personal history of fracture p-value (0.115) nor family history of fracture p-value( 0.110).no significant differences in body mass index between two groups p-value(0.4). Although there was a significant difference for the presence of peripheral neuropathy between two groups, osteoporosis was more common among diabetic patient who have microvascular complication (proteinuria and diabetic retinopathy). Conclusion: T2DM seem to be not a risk factor for osteoporosis unless there is microvascular complication particularly diabetic retinopathy and or nephropathy.